2017
DOI: 10.1002/jtr.2161
|View full text |Cite
|
Sign up to set email alerts
|

The promotion of health tourism products for domestic tourists

Abstract: This study investigates the demand for travel for well‐being and enhancing health by Korean domestic tourists. The current level of health travel preferences and participation rates were examined and compared to the preference for other travel types. A questionnaire survey was conducted with 270 participants, and additional raw data from the Korean National Tourism Survey (a sample of 6,309) were incorporated. This research found that preference for health travel is comparatively high, but participation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…The development of the final health tourism products should be matched with the surrounding tourism resources. The related facilities and layouts involved in the health tourism should be integrated with the surrounding ecological environment [16] [17], so that visitors will not feel awkward when they enjoy the health tourism products.…”
Section: Combination Of Traditional Health Culture and Modern Health mentioning
confidence: 99%
“…The development of the final health tourism products should be matched with the surrounding tourism resources. The related facilities and layouts involved in the health tourism should be integrated with the surrounding ecological environment [16] [17], so that visitors will not feel awkward when they enjoy the health tourism products.…”
Section: Combination Of Traditional Health Culture and Modern Health mentioning
confidence: 99%
“…In the mental health area, Gilbert and Abdullah () showed that travel, specifically vacation experiences, has a positive impact on an individual's subjective well‐being. Han et al () also argue that travel experiences have a positive impact on psychological well‐being. Lee and Jeon () found that more frequent and longer travel activities correlated with greater levels of psychological well‐being.…”
Section: Literature Reviewmentioning
confidence: 79%
“…The study concluded that the group that enjoyed diverse experiences during a weekend trip had more positive psychological results compared with the group who did not go on a weekend trip and that depending on the experiences, emotion, cognition, and social psychological states Gilbert and Abdullah (2004) showed that travel, specifically vacation experiences, has a positive impact on an individual's subjective well-being. Han et al (2018) also argue that travel experiences have a positive impact on psychological well-being. Lee and Jeon (2005) found that more frequent and longer travel activities correlated with greater levels of psychological well-being.…”
Section: Components Of the Travel Experiencementioning
confidence: 99%
See 2 more Smart Citations